2019
DOI: 10.1007/s00432-019-02981-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous loss of keratinocyte TRIM16 expression increases melanocytic cell lesions and lymph node metastasis

Abstract: Purpose The tripartite motif (TRIM)16 acts as a tumour suppressor in both squamous cell carcinoma (SCC) and melanoma. TRIM16 is known to be secreted by keratinocytes, but no studies have been reported yet to assess the relationship between TRIM16 keratinocyte expression and melanoma development. Methods To study the role of TRIM16 in skin cancer development, we developed a keratinocyte TRIM16-specific knockout mouse model, and used the classical two-stage skin carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Previous studies have documented the functions of TRIM16 mainly in cancer, innate immune and other physiological and pathophysiological processes ( Hatakeyama, 2017 ; Sutton et al, 2019 ). To date, the role of TRIM16 in osteogenesis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the functions of TRIM16 mainly in cancer, innate immune and other physiological and pathophysiological processes ( Hatakeyama, 2017 ; Sutton et al, 2019 ). To date, the role of TRIM16 in osteogenesis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the functions of TRIM16 in cancer, innate immune and other physiological and pathophysiological processes [19,27]. To date, the role of TRIM16 in osteogenesis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes are also able to influence melanocytes and melanoma cells through factors secreted to the stroma. Under the influence of UV radiation, keratinocytes secrete tripartite motif-containing protein 16 (TRIM16) [ 46 ]. It was reported that the TRIM16 level in melanoma was lower compared to the normal melanocytes, which also correlated with a rate of lymph node metastasis in TRIM16 LOW melanoma patients.…”
Section: Keratinocytesmentioning
confidence: 99%
“…It was reported that the TRIM16 level in melanoma was lower compared to the normal melanocytes, which also correlated with a rate of lymph node metastasis in TRIM16 LOW melanoma patients. Moreover, BRAF inhibitor treatment increased the TRIM16 production in melanoma cells, while TRIM16-deficient mice exhibited elevated incidence of metastasis compared to the control animals [ 46 , 47 ]. This study supports the thesis that keratinocyte-derived TRIM16 may inhibit melanoma metastasis ( Figure 2 ) [ 46 ].…”
Section: Keratinocytesmentioning
confidence: 99%